2016
DOI: 10.1371/journal.pntd.0004843
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsial Disease in the Peruvian Amazon Basin

Abstract: Using a large, passive, clinic-based surveillance program in Iquitos, Peru, we characterized the prevalence of rickettsial infections among undifferentiated febrile cases and obtained evidence of pathogen transmission in potential domestic reservoir contacts and their ectoparasites. Blood specimens from humans and animals were assayed for spotted fever group rickettsiae (SFGR) and typhus group rickettsiae (TGR) by ELISA and/or PCR; ectoparasites were screened by PCR. Logistic regression was used to determine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
(35 reference statements)
3
29
0
2
Order By: Relevance
“…Similares estudios en la región confirman la participación rickettsial en la etiología del SFAI (20) . La especie Rickettsia asembonensis ha sido previamente encontrada en Sudamérica, infectando ectoparásitos (21)(22)(23) , esta sería la primera vez que es aislada de muestras humanas en el mismo periodo de estudio en el que fueron encontradas habitando en ectoparásitos, pero en regiones no reportadas, lo cual amerita vigilancia epidemiológica efectiva y estudios adicionales para caracterización completa de especies circulantes.…”
Section: Referencias Bibliográficasunclassified
“…Similares estudios en la región confirman la participación rickettsial en la etiología del SFAI (20) . La especie Rickettsia asembonensis ha sido previamente encontrada en Sudamérica, infectando ectoparásitos (21)(22)(23) , esta sería la primera vez que es aislada de muestras humanas en el mismo periodo de estudio en el que fueron encontradas habitando en ectoparásitos, pero en regiones no reportadas, lo cual amerita vigilancia epidemiológica efectiva y estudios adicionales para caracterización completa de especies circulantes.…”
Section: Referencias Bibliográficasunclassified
“…4,11,12 Likewise, the presence of antibodies to SFGR has been confirmed in different human populations in Peru [13][14][15][16] and in pets, establishing its endemicity. 17 Several of these studies have shown the presence of rickettsial infections in the region, ranging from ∼1% to more than 40% seroprevalence. However, there are still gaps in the knowledge of rickettsial diseases in the Americas, such as evaluating the role of amplifier hosts and their specific influence in the ecology of Rickettsia species or targeted studies oriented to certain species, such as R. typhi.…”
Section: Introductionmentioning
confidence: 99%
“…A similar situation occurs with R. asemboensis. It also has a wide distribution worldwide, having been reported in North America and South America, Asia, the Middle East, and Europe [48], although it is associated with a greater number of ectoparasites, including eas, ticks, and mites of domestic and peridomestic animals (C. canis, C. felis, X. cheopis, Pulex irritans, Amblyomma ovale, Rhipicephalus sanguineus, Rhipicephalus microplus, and Ornithonysus bacoti) [49][50][51][52][53]. It has also been detected in monkey blood in Malaysia [54] and in dog blood in South Africa [55].…”
Section: Discussionmentioning
confidence: 99%